Gender disparity in delayed childbearing among medical trainees in Ontario - Friedman, Catherine L; Saliba, Sarah; Janmohamed, Azraa; McNeill, Kestrel; Dason, Shirin; Karnis, Megan F (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Objective: Physicians report high rates of delayed childbearing and are at increased risk of infertility and pregnancy loss. There are limited studies on this topic in the Canadian context, particularly for trainees. Our objective was to explore Ontario medical trainees’ experiences with and knowledge of delayed childbearing, infertility, and fertility treatments.Methods: We administered a cross-sectional survey to all residents and fellows in Ontario. Descriptive statistics, multiple regression, and thematic analysis of free text responses are used to present the findings.Results: 460 trainees responded to the survey. Over half (57%) intentionally delayed childbearing due to medical training, with long working hours being the most cited reason (82%). Cis women were 85% more likely to delay family initiation than cis men. Rates of early pregnancy loss (17%) were similar to that of the Canadian average for this age group, while rates of infertility (14%) were slightly higher. Knowledge gaps were identified, with trainees scoring 62% on knowledge questions around age-related fertility decline and fertility treatment. The majority (73%) felt their programs were supportive of family initiation during training, with top areas for change identified as increased flexibility with working hours, and increased protected time for required extracurricular activities.Conclusion: Trainee physicians in Ontario report high rates of delaying family initiation due to training, with greater impacts on cis women compared to cis men, and slightly higher rates of infertility. Addressing knowledge gaps is one way to empower trainees to make informed family planning decisions going forward.